Rhein alleviates MPTP-induced Parkinson’s disease by suppressing neuroinflammation via MAPK/IκB pathway - Qin, Xin; Wang, Shu; Huang, Juan; Hu, Binbin; Yang, Xingyan; Liang, Liying; Zhou, Rui; Huang, Wei (Frontiers in Neuroscience, 2024)
Background: Parkinson's disease (PD) is a common neurodegenerative disease with a rapid increase in incidence in recent years. Existing treatments cannot slow or stop the progression of PD. It was proposed that neuroinflammation leads to neuronal death, making targeting neuroinflammation a promising therapeutic strategy. Our previous studies have demonstrated that rhein protects neurons in vitro by inhibiting neuroinflammation, and it has been found to exhibit neuroprotective effects in Alzheimer's disease and epilepsy, but its neuroprotective mechanisms and effects on PD are still unclear. Methods: PD animal model was induced by 1-methyl-4-phenyl-1,2,3, 6-tetrahydropyridine (MPTP). ELISA, RT-qPCR, western blot and Immunofluorescence were used to detect the levels of inflammatory 2 cytokines and M1 polarization markers. The protein expression levels of signaling pathways were measured by western blot. Hematoxylin-eosin (HE) staining showed that rhein did not damage the liver and kidney. Two behavioral tests, pole test and rotarod test, were used to evaluate the improvement effect of rhein on movement disorders. The number of neurons in the substantia nigra was evaluated by Nissl staining. Immunohistochemistry and western blot were used to detect tyrosine hydroxylase (TH) and α-synuclein. Results: Rhein inhibited the activation of MAPK/I κ B signaling pathway and reduced the levels of pro-inflammatory cytokines (IL-1β, IL-6 and TNF-α) and M1 polarization markers of microglia in vivo. In a mouse model of PD, rhein ameliorated movement disorders, reduced dopaminergic neuron damage and α-synuclein deposition. Conclusions: Rhein inhibits neuroinflammation through MAPK/I κ B signaling pathway, thereby reducing neurodegeneration, α -synuclein deposition, and improving movement disorders in Parkinson's disease.